Incidence of Clostridioides difficile in patients post loop ileostomy reversal in an Australian tertiary hospital: a retrospective study. Issue 3 (10th December 2021) - Jordan, Stephanie; Hui, Nathan; Doudle, Mark; Von Papen, Michael; Naik, Arun; Lu, Cu Tai; Nolan, Gregory; Cooper, Michelle
Abstract: Introduction: The purpose of a loop ileostomy is to temporarily divert faeces away from a distal anastomosis, to reduce the consequences of anastomotic leak. This ultimately requires a second procedure to restore bowel continuity, which confers risk of complications including the development of Clostridioides difficile infection (CDI). It is hypothesized that patients who undergo loop ileostomy reversal are at increased risk of CDI when compared with other patients undergoing elective colorectal surgical procedures, and that these patients also experience an increased length of stay (LOS). Methods: A retrospective cohort study was performed on all patients who underwent loop ileostomy reversal at the Gold Coast Hospital and Health Service between 1 January 2012 and 31 December 2019. Results: Two hundred and twenty‐eight patients were identified. Eight tested positive for CDI on faecal PCR (3.51%), a higher incidence than that in patients who underwent an elective colorectal surgical procedure during the same period (0.83%) (RR = 4.23). Additionally, median LOS for ileostomy reversal patients was significantly increased in those who also had CDI when compared with those without CDI (11 versus 4 days; P = 0.0003). Conclusion: The study confirmed that the incidence of CDI was higher in those who underwent ileostomy reversal when compared with an otherwise comparable hospital population (elective colorectal surgery patients). Additionally, those patients who underwent ileostomy reversal and had CDI experienced an increased LOS which translates to increased cost to the healthcare system. Further investigation into pre‐operative screening and prophylactic antibiotics should be considered as a measure to mitigate this post‐operative complication. Abstract : This is a retrospective cohort study performed on 228 patients who underwent loop ileostomy reversal at the Gold Coast Hospital and Health Service from 2012 to 2019, to investigate ileostomy reversal as a risk factor for the development of Clostridioides difficile infection (CDI). It demonstrated a higher incidence of CDI in those who had undergone the procedure when compared with other patients undergoing elective colorectal surgical procedures (3.51% versus 0.83%). Additionally, it demonstrated an increased hospital length of stay for those patients (11 versus 4 days; P =0.0003).